R Factor-Mediated Antibiotic Resistance in Serratia marcescens - Cooksey, Robert C. (1976)
Nineteen of 39 multiresistant strains of Serratia marcescens isolated from clinical sources transferred antibiotic resistance to Escherichia coli or Klebsiella pneumoniae recipients. Marcesins and/or phage prevented effective resistance transfer to E. coli and attempts to select marcescin-resistant mutants of the E. coli recipient strain were unsuccessful. Transfer of resistance was demonstrated for all drugs tested except nalidixic acid. Approximately 90% of donors resistant to tobramycin, ampicillin, or carbenicillin transferred resistance to these drugs. High levels of transferred resistance (minimal inhibitory concentration, >2,500 μg/ml) were demonstrated particularly for ampicillin, carbenicillin, and kanamycin. Transmissibility of Serratia R factors was greatest between isogeneic strains of E. coli K-12. Comparative rates of spontaneous loss of R factor-mediated resistance indicated that Serratia R factors are less stable in E. coli and K. pneumoniae transcipients than in the indigenous hosts.